2020
DOI: 10.3390/nano10071307
|View full text |Cite
|
Sign up to set email alerts
|

Improving Plasmonic Photothermal Therapy of Lung Cancer Cells with Anti-EGFR Targeted Gold Nanorods

Abstract: Lung cancer is a particularly difficult form of cancer to diagnose and treat, due largely to the inaccessibility of tumours and the limited available treatment options. The development of plasmonic gold nanoparticles has led to their potential use in a large range of disciplines, and they have shown promise for applications in this area. The ability to functionalise these nanoparticles to target to specific cancer types, when combined with minimally invasive therapies such as photothermal therapy, coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…Although the 808 nm laser wavelength does not correspond to the maximum of the LSPR bands of the core-shell NPs, such a wavelength has been selected for the PT experiments, as it is commonly employed in clinics for various medical procedures [ 57 , 58 ]. Furthermore, the exploitation of the CW laser offers the possibility to irradiate the suspension for a prolonged time, and properly controlling the power density without damaging the nanostructures [ 59 ]. Conversely, high density femtosecond, picosecond or also nanosecond pulsed laser sources can induce detrimental phenomena, such as NCs melting or reshaping [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the 808 nm laser wavelength does not correspond to the maximum of the LSPR bands of the core-shell NPs, such a wavelength has been selected for the PT experiments, as it is commonly employed in clinics for various medical procedures [ 57 , 58 ]. Furthermore, the exploitation of the CW laser offers the possibility to irradiate the suspension for a prolonged time, and properly controlling the power density without damaging the nanostructures [ 59 ]. Conversely, high density femtosecond, picosecond or also nanosecond pulsed laser sources can induce detrimental phenomena, such as NCs melting or reshaping [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results agree with previous studies that identified necrosis as the main in vitro cellular response to PTT, leading to cell membrane rupture, DNA damage and protein denaturation. The passive accumulation of GNPs within cancer tissues, mediated by the enhanced permeability and retention effect, together with the possibility to easily functionalize the gold surfaces with targeting ligands [ 71 ], paves the way to providing robust double-targeting therapy approaches. The latter could exploit the recognition ability of conjugated targeting moieties with the possibility to focus the triggering light radiation at the desired site of action, lowering the collateral damage to healthy tissues, thus working towards a clinical need of crucial importance for the treatment of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Selected wells of the AuNRs + laser and laser only groups were irradiated using a continuous wave diode laser (B4-852-1500-15C, Sheaumann) at 1064 nm with a power density of 2 W/cm 2 (10 mm beam diameter) for a total of 2 min each. The laser was mounted on a 3-axis motorised translation stage, as previously described [ 49 ], and alternate wells were irradiated to minimise bias of overheating of the next well from neighbouring well. Well temperature was recorded using infrared thermal imaging camera (#TIM 640, Micro-Epsilon Messtechnik GmbH & Co. KG).…”
Section: Methodsmentioning
confidence: 99%